2019
DOI: 10.1080/02699206.2019.1595735
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of the prevalence of speech and motor speech disorders in adolescents with Down syndrome

Abstract: Although there is substantial rationale for a motor component in the speech of persons with Down syndrome (DS), there presently are no published estimates of the prevalence of subtypes of motor speech disorders in DS. The goal of this research is to provide initial estimates of the prevalence of types of speech disorders and motor speech disorders in adolescents with DS. Conversational speech samples from a convenience sample of 45 adolescents with DS, ages 10 to 20 years old, were analysed using pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 64 publications
1
25
0
3
Order By: Relevance
“…The well-documented intelligibility deficits in persons with DS and the substantial prevalence of motor speech disorders in adolescents with DS recently reported in Wilson, Abbeduto, Camarata, and Shriberg (2019) motivated the questions posed in the present report. Findings in Wilson et al (2019) indicated that nearly all (97.8%) of the 45 classifiable adolescents with DS in the sample met diagnostic classification criteria for one of the four types of motor speech disorders described previously. In order of prevalence within the sample, 37.8% of the participants met criteria for CD, 26.7% met criteria for SMD, 22.2% met criteria for CD & CAS, and 11.1% met criteria for CAS.…”
Section: Statement Of Purposementioning
confidence: 74%
See 3 more Smart Citations
“…The well-documented intelligibility deficits in persons with DS and the substantial prevalence of motor speech disorders in adolescents with DS recently reported in Wilson, Abbeduto, Camarata, and Shriberg (2019) motivated the questions posed in the present report. Findings in Wilson et al (2019) indicated that nearly all (97.8%) of the 45 classifiable adolescents with DS in the sample met diagnostic classification criteria for one of the four types of motor speech disorders described previously. In order of prevalence within the sample, 37.8% of the participants met criteria for CD, 26.7% met criteria for SMD, 22.2% met criteria for CD & CAS, and 11.1% met criteria for CAS.…”
Section: Statement Of Purposementioning
confidence: 74%
“…Figure 1 is a display of the II scores and OII classifications for the original sample of all 50 children with DS, including the 5 participants whose motor speech status could not be classified due to insufficient data to complete the measure used to classify a speaker as having CAS (Wilson et al, 2019). Two of the five participants excluded from further analyses in the present paper met OII criteria for High intelligibility and the other three met criteria for Low intelligibility.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversational speech samples were available from three comparison groups totaling 104 participants studied in associated research in speech sound disorders. The three groups included 45 participants, 8–20 years old, with DS (Wilson, Abbeduto, Camarata, & Shriberg, 2018); 28 participants, 10–21 years old, with fragile X syndrome (FXS; Abbeduto et al, 2003); and 31 participants, 4–16 years old, with galactosemia (GAL; Shriberg, Potter, & Strand, 2011). As described later in Table 1, participants in these three groups were in the same approximate age range as the present participants with 22q, had a high prevalence of MSDs, and had medical issues and developmental delays, and participants with DS were at a similar greater risk for conductive hearing loss.…”
Section: Methodsmentioning
confidence: 99%